Media Pembelajaran Animasi Reboisasi Hutan untuk Siswa kelas VIII SMA Telkom Puwokerto - Putra, Muhammad Briliantama; Baharsyah, Alzi Mula; Pambudi, Dana Eko Wahyu; Setiawan, Bagus Ahmad; Fahrisena, Ahmad Faishal; Suroso, Setyawan; Aldo, Dasril (JURSIMA, 2022)
Therefore, the animated learning materials available in the market or on the Internet are also much improved. However, there are some gaps or weaknesses in the learning medium like there is no explanation so the teacher has to explain. And the means of displaying material too quickly or without controls make it difficult for students to understand and teachers to rush to explain. Also the vehicle models are not user-friendly. Therefore, based on those shortcomings or weaknesses, SMA Telkom Purwokerto's research on building eco-friendly animation materials for 8th grade students by SMA Telkom Purwokerto aims to make science lessons interesting. taste, efficiency and effectiveness. This study is a method using 2D modeling, definition, design, development and implementation. At the development stage, researchers have to validate the animated learning material, implemented with 2 validators using a validation table to see the realism of the animated learning material, this claim sheet given to teachers and students. The data processing results from the authenticity and practicality of the questionnaires concluded that the developed animated learning aids are valuable in terms of quality and practicality for teachers and students to use. , so it is suitable to be a support medium for scientific learning about greening the environment.